Materials For Biodegradable Bones Based On Fe - Hrabovský, Jan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
The thesis deals with biodegradable bone implants which must have good mechanicalproperties and also good compatibility with the human body. The thesis contains literary research inthe area of bone physiology, biogenic materials and implants for the human body. The thesis focueson the selection of suitable materials for biogenic implants.
Keywords: Biodegradability; implants; bone; iron; corrosion; magnesium